PENEGAKAN HUKUM ADMINISTRASI TERHADAP KEGIATAN YANG TIDAK BERDAMPAK PENTING YANG BELUM MEMILIKI DOKUMEN UKL-UPL (Studi PT. Hadi Putra Makmur Kota Semarang) - Istiqomah Istiqomah (Fakultas Hukum Universitas Stikubank, 2019)
ABSTRACT An environmental permit is a permit given to any person or initiator who wishes to undertake a business and / or activity that is required to be UKL-UPL in the framework of environmental protection and management as a condition of obtaining a business and / or activity license. Violations committed by PT. Hadi Putra Makmur related to the issue of obligations and prohibitions, especially regarding licensing, efforts to manage and monitor the environment, hereby the supervision of DLH enforces by giving administrative sanctions. The above is the basis for the author to take the title